HYDRODYNAMICS OF FLUID TRANSMISSION CAPACITY OF BUBBLE EXTRACTOR FILTER - Karimov Ikromali Tojimatovich; Khursanov Boykuzi Jurakuziyevich (European Science Publishing, 2023)
In the article, a new construction of filter bubble extractor is recommended, its construction structure and working principles are presented. As a result of theoretical studies, empirical equations for calculating the resistance coefficients of the filter and the equation for calculating the liquid permeability, i.e., the liquid speed, depending on these resistance coefficients and the density of liquid mixtures, were recommended. By determining this speed, it is possible to select and design the main parameters of the filter to ensure a stable, non-condensing flow of liquid phases in the mixing zones of the apparatus, and to determine the consumption of light and heavy phases supplied to the apparatus.
Keywords: bubbler, extractor, filter, contact surface, fiber material, base mesh, external mixing zone speed.